Development of Solar Tunnel Dryer For Industrial Use - Singh, Pratap; Rathore, N S; Mathur, A N (Journal of Agricultural Engineering, 2007)
This paper deals with a technology for drying of Di-basic calcium phosphate (DCP) through solar energy. For drying this material a solar tunnel dryer was designed and commissioned at M/S Phosphate India Limited, Udaipur. It is semi-cylindrical shaped tunnel dryer having a loading capacity of 1.5 tonne per batch. Two such tunnels were installed in series to accommodate 3.0 tonne of material. It is observed that maximum temperature inside the solar tunnel dryer was 62degree C and 50degree C on a summer and winter day respectively, which is about 15degree C higher than ambient temperature. Total 16 h were needed for drying DCP up to the safe moisture content during winter seasons while total 12 h were needed during summer seasons for reducing moisture content from 37.3% to 9.4%. The solar tunnel drying reduces moisture content to around 10%. Thereafter, the moisture content is reduced to around 5% in a spin-flash dryer for final delivery to market.